A Formation of Peer Counsellors in an Effort to Create a Youth Information and Counselling Center at SMP Muhammadiyah Banguntapan, Bantul Yogyakarta - Ismarwati Ismarwati; Intan Mutiara Putri; Menik Sri Daryanti; Luluk Dwihestie (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The partner of this community service activity is SMP Muhammadiyah Banguntapan, Bantul, Yogyakarta. Analysis of the problems faced by partners includes the unavailability of Adolescent Counseling Information Centers in the school and the lack of information on adolescent reproductive health. The purpose of this community service activity is to establish a school PIK-R (Pusat Informasi Konseling Remaja) -Youth Counseling Information Center and to provide educators and peer counselors at SMP Muhammadiyah Banguntapan. School’s PIK-R as a guidance forum for teenagers to help them recognizing reproductive health early as a preventive and promotive effort so that it can prevent teenagers from falling into promiscuity. The solutions to the problems given are: 1) Establishing a School Youth Counseling Information Center; 2) Conducting training for school Youth Counseling Information Center administrators; 3) Conducting school Youth Counseling Information Center activities. The method of service was carried out through several stages, namely; The first stage was assessment; The second stage was Planning and development; The third stage was implementation, and the last stage was evaluation. The results of this activity obtained outputs 1) The establishment of a School Youth Counseling Information Center at SMP Muhammadiyah Banguntapan; 2) Availability of peer counselors; 3) One scientific article published in an accredited national journal 4) One article on online media 5) Activity video; 6) Media that obtained Intellectual Property Rights certificates and reports on community service activities. Conclusion. This community service activity went smoothly, and the planned output was achieved. This community service activity has a positive and beneficial impact for the SMP Muhammadiyah Banguntapan of Bantul Yogyakarta. Recommendations for further service activities can be done by refreshing peer counselors and collaborating with the Muhammadiyah Student Association.